A numerical simulation study for controlling seawater intrusion by using hydraulic and physical barriers - Panpan LYU; Jian SONG; Jianfeng WU; Jichun WU (Shuiwen dizhi gongcheng dizhi, 2021)
Seawater intrusion (SI) has become a global concern for groundwater environment. SI not only seriously threatens freshwater resources in coastal aquifers, but also undermines the balance of coastal ecosystem and further restricts the socioeconomic development. This paper simulates the SI process in a 2D synthetic aquifer constructed from sandbox experiment using the simulator SEAWAT-2000. The transport phenomenon of the brackish water interface is investigated by altering the location and injection rate of a recharge well and the layout of the physical barrier. The results show that when the recharge well is located near the toe of the salt water wedge of 40 cm from the coastline and 5 cm from the surface, the optimal performance of the recharge scheme is achieved with the repulsion rate up to 21.5%. When the physical barrier is located 10 cm from the coastline and the penetration depth is 35 cm, the toe of saltwater wedge is effectively driven to the coastline with the repulsion rate up to 81.8%. Moreover, we simulate the variable-density groundwater flow and transport in a typical two-dimensional section of coastal aquifer in the Longkou District of Shandong Province. The SI model is established to evaluate the influences of different management schemes (i.e., physical barrier and recharge well) on the prevention of seawater intrusion. The results show that when the physical barrier is located 600 m from the coastline and the penetration depth is 18 m, the toe of salt water wedge is effectively driven back to the coastline with the repulsion rate up to 28.4%. The results reveal the influence of hydraulic and physical barriers under different settings on the migration rule of the brackish water interface. The findings may provide insights into the optimization suggestions for coastal groundwater management under site conditions.